Pelatihan Penggunaan Aplikasi Adobe Photoshop MGMP Seni Budaya Tingkat SMP Kabupaten Mempawah - Arif, Ibnu; Zulkarnain, Izuardo; Artha Octaviyana, Rickhy; . Tsanauddin Farid, M; Anugrah, Rifqi; Handika Sugasta, Hervian; Puji Santosa, Dimas; Farindi Dwi Puteri, Martsa (Pengelola Jurnal Politeknik Negeri Ketapang Jl. Rangga Sentap, Dalong Sukaharja, Ketapang 78813. Telp. (0534) 3030686 Kalimantan Barat, 2024)
This training activity aims to improve the competence of MGMP Members of Arts and Culture and Junior High School Students of Mempawah Regency in utilizing Adobe Photoshop to support learning. The need for interesting and relevant visual materials for students is the background of this activity. This training was held on August 7 at SMPN 2 Mempawah Hilir. The training method includes material explanations, demonstrations, and hands-on practice, with material covering the basics of Photoshop, Introduction to Adobe Photoshop applications, Visual cropping and colouring techniques on Adobe Photoshop applications and Practice of making poster designs with Adobe Photoshop applications. In practice, participants produce simple graphic design as proof of new competencies obtained in the training process. This training is expected to contribute to improving the quality of cultural arts learning at the junior high school level, where teachers are able to create innovative and interesting learning media so as to increase students' interest and understanding, and students' understanding of making simple designs